Children, teens, families, and mass media : the millennial generation - Kundanis, Rose M., 1947- (LEA's communication series., 2003)
This volume examines children's experiences with electronic media in the home, including children's development of media literacy. To understand the experiences, the book examines the children at various developmental ages and across generations.